Trade-offs or synergies?: assessment of ecosystem services in multi-use small reservoirs in Burkina Faso [Abstract only] - Balana, Bedru (2015)
Small reservoirs (SRs) development, as a strategy to enhance food and water security in water-scarce regions, has long attracted the interests of governments and development agents. The main argument put forward was that by providing water for small-scale agriculture, they can cushion the impacts of drought and rainfall variability on vulnerable and less-developed regions. Because of the dominance of interests in small-scale irrigation, performance assessments of SRs have concentrated on irrigation outcomes. The multiple non-irrigation uses/benefits and potential negative externalities were largely neglected in the measurement of their performance. The publication of Millennium Ecosystem Assessment in 2005 triggered the concept of ‘ecosystem services’ and prompted both academia and policy decisions to consider multiple effects/impacts of human activities on natural capital, ecosystem services, and human wellbeing. Along the lines of the surge in thoughts in ‘ecosystem services’, SRs, besides irrigation use, could generate multiple benefits such as improved access to domestic water, enhance women’s position, recreation, livelihood diversification, fisheries, water availability for livestock, limiting floods, and increased biodiversity. On the other hand, SRs may have unwanted side-effects such as environmental deterioration, decrease in water quality, adverse health impacts (e.g., harbour mosquitos), and reduce environmental flows and ground water recharge. Thus, SRs’ performance need to be assessed against these multiple benefits/dis-benefits and whether there exist trade-offs or synergetic relationship.